Mucormycosis in COVID-19 Patients – A Case Series from a Dental College in South India - Annapoorani Sevagaperumal; A. Christy Winnifred; T. Jones R. Deva Thambi (Indian Journal of Dental Research)
Introduction: Incidence of mucormycosis has increased recently due to rapid spread of coronavirus disease 2019 (COVID-19), which is a hyper-ferritemic state paving a way for easy growth of mucor species. COVID-19 infection results in an immunocompromised state due to the steroid therapy administered to patients and the infection itself. The presence of co-morbidities makes patients more susceptible to acquire mucor infection. Mucormycosis spreads rapidly, associated with aggressive angioinvasion, leading to ischemic necrosis of surrounding tissues. Due to its rapid spread and angioinvasion, mucormycosis is associated with increased mortality and morbidity. Treatment Planning: Early diagnosis and proper treatment planning are crucial to prevent further spread of infection, where dentists play an important role. Discussion: This case series is mainly focused on patients reported to the oral medicine department with complaints of discomfort or mobility of teeth in the maxillary region while explaining the role of dentists in diagnosing and treating the disease.